Anthraquinone-2-Carboxylic Acid Is a Potential Antiviral Candidate Against Influenza Viruses In Vitro and In Vivo - Sichen Ren; Yan Luo; Huimin Tao; Ping Wang; Song Li; Jingjing Yang (Viruses)
Seasonal outbreaks and occasional pandemics triggered by influenza viruses annually impose considerable burdens on public health and finances. The continual evolution of viral strains with drug resistance emphasizes the urgency of discovering novel agents for influenza viruses. This study investigated a set of innovative substances derived from Morinda officinalis with antiviral potential against influenza virus strains. The top candidate, anthraquinone-2-carboxylic acid (A2CA), presented antiviral activity against diverse influenza virus strains, including those resistant to oseltamivir. In an influenza mouse model, the pre-administration of A2CA dose-dependently ameliorated influenza A virus (IAV)-mediated weight loss as well as protected mice from a lethal IAV infection. In addition, lung injury and cytokine dysregulation were mitigated. Further investigation revealed that IAV-induced activation of the RIG-I/STAT1 signaling pathway did not occur after A2CA treatment. A time-of-addition assay revealed that A2CA targeted the final phase of intracellular replication, which was further determined by molecular docking between A2CA and the IAV RdRp protein. Finally, transcriptome analysis revealed that the TP53TG3C, CFAP57 and SNX30-DT genes may be involved in the antiviral effects of A2CA. These results play a part in achieving a thorough comprehension of the capacity of A2CA to inhibit influenza virus infection.